The Study on Effects and Efficiency of Cognitive Behavioral Treatment among Prisoners in India - Sundaram, B. Leelesh (International Journal of Psychosocial Rehabilitation, 2020)
As a result of pressing recommendations made by NGOs and Human rights commission, the reforms taken by the legislature and executive abiding to the interventions of judiciary has led to implementation of cognitive behavioural treatments of prisoners as a step of reformation, which appears to be a suitable one in theory since prisoners have distorted cognitions. Various studies have put forth that cognitive behavioural treatments often has certain adverse effects for which categorized treatments are given. However research has failed to note these effects of cognitive behavioural treatment in the case of prisoners. Thus in this case it becomes mandatory to recognise the existence of effects of Cognitive behavioural treatment. At the same time rate of habitual offenders show a steady inclination in spite of reformation through cognitive behavioural treatment, which gives scope for ambiguity with relation efficiency of the current reformation practice. Hence this research is carried out to identify the effects of cognitive behavioural treatment among prisoners and its efficiency. By the virtue of non probability convenience sampling method with a sample size of and using statistical tools such as chi square and correlations it could be found out that prisoner undergoing cognitive behavioural treatments are subjected to deterrent effects arising out of frustration and anxiety which may include stress, depression and mood swings etc and also have deterrent flashbacks of the crimes or actions committed in past. The study helps in finding out that cognitive behavioural treatments lack efficiency. The recommendation put forth by this study is that Prisons should adopt performance and management techniques which are similar to the New York Police Department's COMPSTAT method for tracking the progress and promoting the safety of prisoners, which would thereby promote hygiene factors as laid down under the Herzberg – Two factor theory